Non-cardiac complications during pregnancy in women with isolated congenital pulmonary valvar stenosis. Issue 12 (3rd July 2006) - Drenthen, W; Pieper, P G; Roos-Hesselink, J W; Schmidt, A C M; Mulder, B J M; van Dijk, A P J; Vliegen, H W; Sollie, K M; Voors, A A; Ebels, T; van Veldhuisen, D J
Abstract : Background: Information on the outcome of pregnancy in patients with pulmonary valvar stenosis is scarce, mostly limited to cardiac complications observed during pregnancy. Objectives: To investigate the magnitude and determinants of non-cardiac and fetal risks during pregnancy of women with isolated pulmonary valvar stenosis. Methods: Using the nationwide registry (CONgenital CORvitia), 106 women with (un-)corrected pulmonary valvar stenosis receiving care in six tertiary medical centres in The Netherlands were included. A total of 51 women had 108 pregnancies, including 21 (19%) miscarriages and 6 elective abortions. Results: In the 81 completed (>20 weeks of gestation) pregnancies, we observed a high number of hypertension-related disorders (n = 12, 15%, including pre-eclampsia (n = 4) and eclampsia (n = 2)), premature deliveries (n = 14, 17%, including one twin) and thromboembolic events (n = 3, 3.7%). Furthermore, recurrence of congenital heart defects in the offspring was detected in three children (3.7%, pulmonary valvar stenosis (n = 2) and complete transposition of the great arteries in combination with anencephaly). In addition to the intrauterine fetal demise of the transposition child, three other children died shortly after birth owing to immaturity, hydrocephalus combined with prematurity and meningitis (overall offspring mortality, 4.8%). Conclusion: In this largest report on pregnancy in women with (un-) corrected isolated pulmonary valvar stenosis, an excessive number of (serious) non-cardiac complications and mortality were observed in the offspring.